ON THE REFINEMENT OF ONE ESTIMATE OF THE SCALAR WAVE FIELD SCATTERED BY AN IMPEDANCE SPHERE - Krapivnoy, A. V.; Chumachenko, V. P.; Chumachenko, Y. V. (Radio Electronics, Computer Science, Control, 2024)
The problem of scalar plane-wave scattering off a reactively loaded sphere is examined. The features of a new approach, which is close to the physical optics approximation and considers (in its initial variant) the curvature of the target at the plane of incidence, are studied. It is shown, that possible consideration of the curvature at the plane perpendicular to the plane of incidence improves the estimate of the scattered field, but this improvement is not so essential as in the case of change from physical optics to the initial variant of the method considering the curvature at only one plane.